Penetapan Tujuan Pendidikan Islam dalam Silabus Pembelajaran - Al Kautsary, Muhammad Iqbal Al Kautsary; Nugraha , Mulyawan Safwandy (NIẒĀMUL`ILMI : Jurnal Manajemen Pendidikan Islam, 2024)
This article examines the important role of curriculum implementation in Madrasah Aliyah Negeri 3 Karawang, which has a significant impact on the determination and achievement of educational goals. The curriculum as the main educational tool plays a central role in curriculum planning and implementation, especially in a madrasah environment rich in Islamic values. The curriculum is, first and foremost, a structured guide that provides a basis for outlining learning objectives. By clearly stating the objectives, teachers can devise appropriate learning strategies to meet the needs of the madrasah. The first priority when creating a curriculum is to focus on achieving students' overall educational goals, including spiritual, academic and social aspects. The article also highlights the importance of coherence between the curriculum, madrasah vision and Islamic education goals. By ensuring that the espoused religious values and principles of the madrasah are reflected in the curriculum, the spiritual and moral dimensions of learning can be incorporated into the curriculum. In addition, the article highlights the role of continuous assessment as an integral part of curriculum implementation. Periodic evaluation helps measure the achievement of educational objectives, provides necessary feedback and allows for the adjustment of the curriculum in relation to the evolving context of the madrasah. By combining theoretical perspectives and empirical findings, this article aims to provide a holistic understanding of how the existing curriculum implementation at MAN 3 Karawang can shape and guide the educational objectives in the madrasah. Practical implications and policy recommendations are included to guide the school in optimizing the role of the curriculum as a key tool to fulfill its educational mission. Keyword : Vision Madrasah, Education Curriculum, Evaluation